The number of microvascular complications is associated with an increased risk for severity of periodontitis in type 2 diabetes patients: Results of a multicenter hospital‐based cross‐sectional study. Issue 5 (8th May 2017) - Nitta, Hiroshi; Katagiri, Sayaka; Nagasawa, Toshiyuki; Izumi, Yuichi; Ishikawa, Isao; Izumiyama, Hajime; Uchimura, Isao; Kanazawa, Masao; Chiba, Hiroshige; Matsuo, Akira; Utsunomiya, Kazunori; Tanabe, Haruyasu; et al.
Abstract: Aims/Introduction: To explore the relationships between periodontitis and microvascular complications as well as glycemic control in type 2 diabetes patients. Materials and Methods: This multicenter, hospital‐based, cross‐sectional study included 620 patients with type 2 diabetes. We compared the prevalence and severity of periodontitis between patients with ≥1 microvascular complication and those without microvascular complications. We also compared the prevalence and severity of periodontitis among patients with different degrees of glycemic control. Results: After adjusting for confounding factors, multiple logistic regression analysis showed that the severity of periodontitis was significantly associated with the number of microvascular complications (odds ratio 1.3, 95% confidence interval 1.1–1.6), glycated hemoglobin ≥8.0% (64 mmol/mol; odds ratio 1.6; 95% confidence interval 1.1–2.3), and older age (≥50 years; odds ratio 1.7; 95% confidence interval 1.1–2.6). However, the prevalence of periodontitis was not significantly associated with the number of microvascular complications, but was associated with male sex, high glycated hemoglobin (≥8.0% [64 mmol/mol]), older age (≥40 years), longer duration of diabetes (≥15 years) and fewer teeth (≤25). Furthermore, propensity score matching for age, sex, diabetes duration and glycated hemoglobin showed that the incidence of severe periodontitis was significantly higher among patients with microvascular complications than among those without microvascular complications ( P < 0.05). Conclusions: The number of microvascular complications is a risk factor for more severe periodontitis in patients with type 2 diabetes, whereas poor glycemic control is a risk factor for increased prevalence and severity of periodontitis. Abstract : We explored the relationship between microvascular complications and periodontitis, and glycemic control status and periodontitis in type 2 diabetic patients in a multicenter hospital‐based cross‐sectional study. We found that severity of periodontitis was significantly associated with the number of microvascular complications, but the prevalence of periodontitis was not. Thus, we presume that diabetic microvascular complication can be designated as a risk factor for the increased risk for periodontitis through increasing the severity of periodontitis in type 2 diabetic patients.